RBV and the road to the control of external organizations - Jörg Freiling (Management Revue, 2008)
Although primarily focusing on the internal resource endowment of the firm, RBV has the potential to address the firm's embeddedness in the business environment as well. At present, RBV research lacks a sound understanding of the development of competitive advantages in industries. A change regarding the unit of analysis, however, allows for considering causes and effects on the micro and the macro level as well. The paper stresses the entrepreneurial dimension of RBV and the firm's impact on the environment by comparing RBV and RDA reasoning. Using the explanatory power of the isolating mechanisms and applying system dynamic modelling, it turns out that RBV can move into the direction of a 'New IO'.
Keywords: 650; Resource-based View; resource dependence approach; structural school; process school; inter-organizational dependence; power; entrepreneurship theory; open system view; system dynamic modelling